Chromosomal profile of Deccani sheep - PRAKASH, M GNANA; RA0, G NARASIMHA; GUPTA, B RAMESH; VENKATRAMAIAH, A; REDDY, G V NARASA (The Indian Journal of Animal Sciences, 2011)
The present study was conducted to standardize the karyotype profiles and various morphological and Inorphometric characters of chromosomes of Deccani sheep. The diploid chromosome number in Deccani sheep was 54. All the autosomes were acrocentric except the first three pairs, which were sub-metacentric. The X chromosome was the longest acrocentric, while Y-chromosorne was the slnallest hi-armed chromosome. Sex of the animal had a nonsignificant influence on the morphometric measurements of all the chromosomes, while the differences among the chromosomes were significant. The mean relative length of autosomes varied from 1.78 to 9.35%. The X- and Y- chromosomes contributed 5.05 and 1.70% of the total genome, respectively. The means for the ann ratio, centromeric index and morphological index of the sub-metacentric autosomes 1, 2 and 3 varied from 1.17 to 1.20, 0.54 to 0.55 and 9.40 to 11.57, respectively. The G-banding pattern of the chromosomes in Deccani sheep more or less matched with the standard karyotypes. All the autosomes revealed centromeric C-hands. The nucleolar organizer regions were detected on chromosomes 1, 2,3,4 and 25.Â